Characterization of Encapsulation Process of Avobenzone in Solid Lipid Microparticle Using a Factorial Design and its Effect on Photostability - Cecilia Gallardo Cabrera, Juan Fernando Pinillos Madrid, Jhonathan David Pazmiño Arteaga, Alejandro Munera Echeverry (Journal of Applied Pharmaceutical Science, 2014)
Avobenzone (AVO)liposphereswere obtained using as encapsulating material carnauba wax and applying the method of hot emulsification. A factorial design 23 was performed to optimize and recognize the influence of the initial amount of AVO, the stearyl alcohol (SA) and polysorbate (PS-20)concentrationsin the AVO loading, mean and D90 particle size. The results showed a variation of AVO loading between 1.8 and 20%, which was mainly affected by initial amount of AVO. The mean particle size D [4.3] ranged from 11.11 to 37.15 μm, this was affected by the levels of SA and PS-20, while D90 was influenced by three variables under study. Lipospheres highly loaded and under a narrow particle distribution was obtained when initial amount of AVO, SA and PS-20 were set in the maximum level. The study showed that the encapsulation process enhanced the photostability going from 31.5% for free AVO to 16.2% for the encapsulated AVO.
Keywords: Avobenzone, solid lipid microparticles, lipospheres, photodegradation.